2009
DOI: 10.1111/j.1600-0404.1992.tb06041.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oxcarbazepine and carbamazepine on the central nervous system: computerised analysis of saccadic and smooth-pursuit eye movements

Abstract: Oxcarbazepine (OXC) is a new anti‐epileptic agent structurally related to carbamazepine (CBZ). OXC seems to have a similar efficacy and a better tolerability profile than CBZ. In the present study we compared the subclinicai side‐effects on the CNS of OXC and CBZ using a computerised analysis of saccadic and smooth‐pursuit eye movements. Six healthy male volunteers (mean age 29 yrs) participated in the study, which was conducted by a double‐blind cross‐over design. Each subject was given a single dose of eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…The primary finding of this study is that AEDs can affect saccades. Previous studies also support our findings, but those studies were performed in healthy volunteers and compared the effects between AEDs [12][13][14][15][16][17][18]. This study is the first systematic approach to determine whether the AEs of AEDs can be assessed using the eye movements obtained with VEOG.…”
Section: Discussionsupporting
confidence: 85%
“…The primary finding of this study is that AEDs can affect saccades. Previous studies also support our findings, but those studies were performed in healthy volunteers and compared the effects between AEDs [12][13][14][15][16][17][18]. This study is the first systematic approach to determine whether the AEs of AEDs can be assessed using the eye movements obtained with VEOG.…”
Section: Discussionsupporting
confidence: 85%
“…8 It has also been found that OXC caused subtle visual alterations together with saccadic and smooth-pursuit eye movements. 18 To the best of our knowledge, there is no animal or postmortem study in the literature investigated the underlying changes or mechanisms of these visual disturbances encountered secondary to these agents used for the treatment of epilepsia. There is only one clinical study investigating the relationship between ocular symptoms and retinal anatomy by using OCT. 5 OCT is a useful clinical tool that can measure the thickness of retinal nerve fiber layer and macula.…”
Section: Discussionmentioning
confidence: 99%
“…Mean RGC number in group 1 (control) was 16.4 AE 5.3 (9-28). In group 2 (VPA), RGC number was 14.0 AE 3.1 (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) and the difference between groups 1 and 2 was not found to be statistically significant (p: 0.128). On the other hand, RGC numbers in group 3 (OXC) and group 4 (combined OXC-VPA) were 12.5 AE 2.7 (8-18) and 10.0 AE 1.9 (6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Rgc Countmentioning
confidence: 99%
“…A reduction in smooth pursuit gain has also been reported (Bittencourt, Gresty, & Richens, 1980; Hoffmann et al, 1993) although this effect has not been consistent (Holzman et al, 1975; Noachtar et al, 1998; Pieters et al, 2003; Tedeschi et al, 1989). In a comparison of the effect on smooth pursuit performance of carbamazepine vs. a newer structurally similar agent, oxcarbazepine, in a double blind cross-over design, carbamazepine reduced tracking velocity to a greater degree than oxcarbazepine (Zaccara et al, 1992). …”
Section: Pharmacologic Effects On Eye Movements In Healthy Individmentioning
confidence: 99%